Assessing Vulnerabilities to Corruption in Public Procurement and Their Price Impact - Abdou, Aly (IMF Working Papers; Working Paper, 2022)
Public procurement can be highly vulnerable to corruption. This paper outlines a methodology and results in assessing corruption risks in public procurement and their impact on relative prices, using large databases on government contracts and tenders. Our primary contribution is to analyze how price differential in public procurement contracts can be explained by corruption risk factor (aggregated in a synthetic corruption risk index). While there are intrinsic limitations to our study (price differentials can come from structural reasons, such as a limited number of potential suppliers) it still provides a guiding tool to assess where corruption risks would have the biggest budgetary impact. Such analysis helps inform mitigating policies owing to the granular data used.